Análise do comportamento estrutural e projeto de uma edificação em Light Steel Frame segundo critérios de dimensionamento aplicados no Brasil - Moreira, Fernanda Frasson (2017)
This paper aims to analyze the Light Steel Frame constructive technology, the approach begins with the history, definition and structural characteristics of the Light Steel Frame. It also addresses the theoretical analysis of the the elements that compose the LSF structure, as well the definition of structural analysis methods within the standard for designing cold-formed profiles structures of steel. At the end, there is the development of the architectural project and the conception structural design of a single-family residence as result of the research.